A cross sectional analysis of perinatally HIV-infected (PHIV) adolescents in a paediatric infectious diseases clinic in the Western Cape, South Africa - Van Heerden, Linda (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.